Case Report: Successful retrieval of a migrated left atrial appendage occluder through the synergistic use of a guidewire and a gooseneck snare - Bao, Yue; Yi, Hongwei; Ma, Jun; Han, Hongwei (Frontiers in Cardiovascular Medicine, 2024)
Left atrial appendage occluder (LAAO) dislodgement with embolization is a rare occurrence. If the LAAO migrates into the left atrium or ventricle, it can lead to acute heart failure or even death, necessitating urgent surgical intervention. Currently, most cases of LAAO dislodgement are managed through open-heart surgery, while percutaneous retrieval of the LAAO has only been reported in a few cases with limited associated experience (1). This article reports a case in which a migrated LACbes device was successfully retrieved using a catheter-based approach, demonstrating an innovative and minimally invasive treatment strategy.